Determinants of the Merger Performance of BUMN Sharia Banks - Ayi Wahid (Research Synergy Foundation, 2021)
Background - The phenomenon of the merger of state-owned Islamic banks (BUMN) was predicted to provide increased financing and operational efficiency which has implications for an increase in the level of operating income and profitability. Purpose – The purpose of the research was to examine and analyze the effect of the level of financing to deposit ratio and the level of efficiency of operating income on profitability as measured by return on assets, either directly or indirectly through the net operating margin. Design/methodology/approach – The research method used was quantitative method with a sample size of 60 which was sourced from quarterly reports at the Financial Services Authority (OJK) which was a combination of cross-sectional data from three state-owned Islamic bank companies (Bank Mandiri Syariah, BNI Syariah, and BRI Syariah. ) during the 2015-2019 period. Data analysis in this research used a panel data regression model with the EViews data processing application program Findings – The results showed that by using a significance level of 5%, financing to deposit ratio and operating costs operating income had an effect but not significantly on the net operating margin. Financing to deposit ratio and operating costs operating income directly have a significant effect on return on assets. However, indirectly through the net operating margin, it can be seen that the financing to deposit ratio has an effect but had not significant on return on assets, on the other hand, operating expenses have a negative and significant effect on return on assets. Other findings from this research indicate that the net operating margin variable has not a mediating variable on the effect of financing to deposit ratio on return on assets, on the other hand, the net operating margin variable had a mediating variable on the effect of operating expenses on operating income on return on assets.. Research limitations– The research only includes two independent variables, this is more due to the cross sectional data used is limited to three state-owned Islamic bank companies with panel data regression models. It is recommended for further research to include other independent variables with a multivariable regression model so that it can provide results on improving the performance of Islamic banks after the merger. Originality/value – The results of statistical testing show that the financing to deposit ratio and operating costs operating income have an effect on but not significant to the net operating margin in the merger of BUMN Islamic banks.